2020
DOI: 10.1016/j.ebiom.2020.102732
|View full text |Cite
|
Sign up to set email alerts
|

Reanalysis and reclassification of rare genetic variants associated with inherited arrhythmogenic syndromes

Abstract: Background: Accurate interpretation of rare genetic variants is a challenge for clinical translation. Updates in recommendations for rare variant classification require the reanalysis and reclassification. We aim to perform an exhaustive re-analysis of rare variants associated with inherited arrhythmogenic syndromes, which were classified ten years ago, to determine whether their classification aligns with current standards and research findings. Methods: In 2010, the rare variants identified through genetic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 28 publications
5
37
0
1
Order By: Relevance
“…In 2020, Campuzano et al analyzed how many variants of genes involved in IAS had to be reclassified after 10 years [118]. The authors found that the 69.23% and the 94.11% of the variants found in, respectively, clinical and forensic cases had to be reclassified and that many of the variants previously classified as likely pathogenic were re-classified as variants of uncertain significance (VUS).…”
Section: Molecular Autopsymentioning
confidence: 99%
“…In 2020, Campuzano et al analyzed how many variants of genes involved in IAS had to be reclassified after 10 years [118]. The authors found that the 69.23% and the 94.11% of the variants found in, respectively, clinical and forensic cases had to be reclassified and that many of the variants previously classified as likely pathogenic were re-classified as variants of uncertain significance (VUS).…”
Section: Molecular Autopsymentioning
confidence: 99%
“…Other studies already pointed out the importance of reanalysis of sequencing data, especially in patients with complex genetic diseases, as genomic databases are continuously updated and adjusted based on new findings in co-segregation studies and functional analyses [44]. Accordingly, when comparing our previously published data and the results presented in this study, some variants were interpreted differently and some new variants popped up.…”
Section: Discussionmentioning
confidence: 73%
“…Similar results were obtained in other studies, which reported a prevalence of 35%-40% of new mutations, half of which were unique for a family[ 136 ]. The conclusive classification of VUS is encumbered by challenges, particularly in cases of “private” mutations, as it involves computational and population-based studies, not rarely misleading[ 137 , 138 ]. Combined use of recent technologies such as iPSC and gene editing have enabled functional annotation in specific cases.…”
Section: Modeling Variants Of Uncertain Significancementioning
confidence: 99%